Perceived Stress in a Gender Perspective: A Survey in a Population of Unemployed Subjects of Southern Italy - Costa, Chiara; Briguglio, Giusi; Mondello, Stefania; Teodoro, Michele; Pollicino, Manuela; Canalella, Andrea; Verduci, Francesca; Italia, Sebastiano; Fenga, Concettina (Frontiers in Public Health, 2021)
Stressful life events are differently handled by women and men. This study evaluates gender differences in perceived stress and health status among a sample of subjects going through a transition period from unemployment to work. This cross-sectional study enrolled 395 participants, 245 men (62%) and 150 (38%) women, between 19 and 67 years, that were going to be hired for a six-month contract. Before being employed, all participants underwent a mandatory protocol consisting in a general medical check. Stress assessment was performed by using the Perceived Stress Scale (PSS). Most of the participants (68%) showed normal to low perceived stress. But dividing the sample by gender, out of the remaining 32% with medium to high stress level, 11% male subjects and 22.7% females reported high perceived stress values. We found mean PSS values that are overlapping with those in the general population of developed countries. This study does not suggest an association between perceived stress and health or social parameters. However, our results highlight that the female gender is associated with higher stress level, pointing out the relevance of specific and designed interventions in the context of health promotion programs, especially in order to mitigate stress in more susceptible subjects.